2007
DOI: 10.1021/ja066455r
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Pyrimidine Ribonucleotide:  Synthesis, Enzymatic Incorporation, and Utilization

Abstract: Fluorescent nucleobase analogs that respond to changes in their microenvironment are valuable for studying RNA structure, dynamics and recognition. The most commonly used fluorescent ribonucleoside is 2-aminopurine, a highly responsive purine analog. Responsive isosteric fluorescent pyrimidine analogs are, however, rare. Appending 5-membered aromatic heterocycles at the 5-position on a pyrimidine core has recently been found to provide a family of responsive fluorescent nucleoside analogs with emission in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
158
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 75 publications
7
158
0
Order By: Relevance
“…In most cases the dNTP modifications were introduced to the nucleobase. In cases where pyrimidines are employed the modifications are almost exclusively at the C5 position to avoid disturbing of Watson-Crick base pairing ability (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In addition, the C5 modification is well accommodated into the major groove of DNA without perturbing the DNA structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases the dNTP modifications were introduced to the nucleobase. In cases where pyrimidines are employed the modifications are almost exclusively at the C5 position to avoid disturbing of Watson-Crick base pairing ability (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In addition, the C5 modification is well accommodated into the major groove of DNA without perturbing the DNA structure.…”
mentioning
confidence: 99%
“…Mainly C5 alkyne modified dNTPs are used because they are accessible via metal mediated cross coupling reactions (21-23) in a straightforward manner. While many C5 modified dNTP analogs are already applied, because they are processed by DNA polymerases at least to some extent, it is still unpredictable which modification will be accepted (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) because the detailed molecular mechanism by which C5 modifications are accepted by a DNA polymerase is not at all understood. This is largely due to the absence of suitable structural data.…”
mentioning
confidence: 99%
“…28 We have also demonstrated that T7 RNA polymerase recognizes this modified ribonucleoside triphosphate as a substrate in run-off in vitro transcription reactions and very efficiently incorporates it into RNA oligonucleotides. We have further illustrated that fluorescent RNA constructs, generated in this fashion, can be employed for the development of biophysical assays.…”
Section: Triphosphate Synthesis and Incorporationmentioning
confidence: 86%
“…Specifically, we have applied this method for the examination of a fluorescent bacterial A-site and its interactions with aminoglycoside antibiotics. 28 Here we employ similar experimental procedures for the preparation of fluorescently tagged TAR constructs as described below.…”
Section: Triphosphate Synthesis and Incorporationmentioning
confidence: 99%
See 1 more Smart Citation